THE RAPIDLY CHANGING ENERGYSECTOR OF INDIA - Sheth, Deepesh; Zinzuvadia, Dev (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper examines the rapidly changing energy sector in India, focusing on the strategies and adaptations of three major players: Reliance Industries, Tata Power, and Adani Power. It analyzes their pre-pandemic renewable energy investment strategies, financial approaches, and working capital management. The paper then delves into the impact of COVID-19 and the Ukraine-Russia war on these companies, highlighting their resilience and vulnerabilities. Finally, it concludes by emphasizing the need for adaptation, innovation, and a focus on clean energy as key drivers for success in the future Indian energy landscape.